THE USE OF CODE SWITCHING BY LECTURERS IN TEACHING PROCESS AT UNIVERSITY OF MUHAMMADIYAH SORONG - Hasanudin Hasanudin (Qalam : Jurnal Ilmu Kependidikan, 2016)
Abstract(The Use of Code Switching by Lecturers in Teaching Process at University of Muhammadiyah Sorong| Code Switching is a process of language which intentionally or unintentionally people talk affected by situation and topic with inserted other language when speaking their language. There were three main problems of this research (1). How often do the lecturers make code switching in the learning process? (2). What are types of code switching that used by lecturers in the learning process? (3). What are the factors cause the lecturers used code switching in the learning process? The method of this research was descriptive gualitative. To gain the data, this research used a recording device, field notes, and a guestionnaire. After analyzing the data, it concluded that all of the lecturers used code switching in the teaching learning process more than 244 occurrences of code switching and more 86.67Yâ€6 responded agree that they often did code switching when teaching. They did code switching based on their material and orally. The writer also found the English codes with added Indonesian prefix and suffix likes dismoothkan, diprint out, utilizingnya, etc. Then, freguently of the codes were Fisheries Faculty 111 of occurrences (45.49â€o) Engineering Faculty 59 (24.180), Law of Faculty 25 (10.25Y9), Sociology Faculty and Administrative Science 25 (10.25Y6) and the remaining 24 occurrences (9.84â€6) are Agriculture Faculty. About 54 statements that shown as situational code switching and nine statements were metaphorical code switching. And ten out 15 factors that the lecturers agree from statements contained in the guestionnaire and five factors were disagreed.